Studi Pengetahuan Masyarakat Dongkala Terhadap Daun Belimbing Wuluh (Averrhoa bilimbi.L) Sebagai Pencegahan Hipertensi - Andi Nurpati Panaungi; Hasma Hasma; Melan Mawarni (Universitas Borneo Lestari, 2024)
Traditional medicine is a type of medicine that is made entirely from plants and is used for therapy. Traditional medicine is also passed down from generation to generation in an effort to preserve the culture that must be preserved. Starfruit is a species in the starfruit family (Averrhoa). Wuluh starfruit leaves are also a traditional medicine used to prevent hypertension. Hypertension is a health problem that is quite dangerous throughout the world because hypertension is the main risk factor that leads to cardiovascular disease such as heart attack, heart failure, stroke and kidney disease, of which in 2016 ischemic heart disease and stroke became the two main causes of death in world. This research aims to determine the knowledge of the Dongkala community regarding starfruit leaves as a prevention of hypertension. The type of research carried out was descriptive research carried out in May and June by distributing questionnaires to people who live in Dongkala Village, Pasarwajo District with a population of 2,439 people with a sample of 96 people using a questionnaire. The results obtained from this research are the evel of knowledge for those aged 40-44 years with a percentage of (25%), the level of knowledge based on gender, namely women with a percentage of (62.5%), the level of knowledge based on education, namely SMA/SMK-S1 level with percentage (50%), and the highest level of knowledge for the Dongkala Village community is with a percentage (61.5%).